Strategy of Developing Oral Vaccine Candidates Against Co-infection of Porcine Diarrhea Viruses Based on a Lactobacillus Delivery System - Guo, Tiantian; Gao, Chong; Hao, Jianhui; Lu, Xiao; Xie, Kun; Wang, Xiaona; Li, Jiaxuan; Zhou, Han; Cui, Wen; Shan, Zhifu; Jiang, Yanping; Qiao, Xinyuan; et al. (Frontiers in Microbiology, 2022)
The trend of multiple porcine diarrhea viruses co-infection has become serious in recent years, and mucosal immunity through oral immunization is an effective way to control these pathogens. To generate a multi-pathogen vaccine against viral co-infection, we employed the Lactobacillus vector platform, previously used to generate potent candidate vaccines against various diseases. Two strategies were adopted to test the protective efficiency of recombinant lactobacillus against multiple diarrhea viruses. One was a mixture of recombinant Lactobacillus expressing antigens of TGEV, PEDV, and PoRV separately. The other is recombinant Lactobacillus expressing antigen fusion protein of the above viruses. Newborn piglets immunized with recombinant Lactobacillus have specific mucosal and humoral immune responses to all three viruses and are protected against severe diarrhea and intestinal pathology. Our results highlight the potential of an oral multi-pathogen vaccine based on the Lactobacillus approach to prevent the transmission and limit the severity of viral co-infection.